A Critical Study of M.G. Vassanji’s Amriika (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Among the community of diasporic authors, M G Vassanji is a well-known figure. He has written an array of well recognised novels, non-fiction books, and collections of short stories. His writings are renowned for their unique and exceptional depiction of the life of migrants.The novel Amriika by Vassanji (1999) perfectly captures the existential, political, cultural, moral, and religious struggles faced by immigrants in the US. The novel tells the untold story of a minority community's history of relocation rather than being a typical tale of migration. Ramji, the protagonist and narrator of Amriika, is a member of the diverse Tanzanian Shamsi Muslim Cutch-Gujarati community. He travels from Dar es Salaam to Cambridge to attend a technical institute. He finds the comfort and glitz of American living to be captivating. Still, he is taken aback by the predicament Americans face in relation to faith and cultural norms. After encountering political instability and racial prejudice, Ramji learns the value of the depth of his cultural heritage. Ramji has been depicted as being connected to his native land throughout the story. He even splits with his first wife for this and moves to California to live with Rumina.However, eventually Rumina vanishes as well, leaving Ramji homeless and unsure of his whereabouts- a prominent predicament faced by all migrants worldwide.My paper explores the immigrants social, cultural, religious, historical, and political itineraries in America, a place assumed as a land of opportunity and aspirations.